PENGARUH LITERASI KEUANGAN DAN PERENCANAAN KEUANGAN TERHADAP KESIAPAN FINANSIAL MASA PENSIUN MELALUI SIKAP KEUANGAN PADA PT. PLN (PERSERO) UP3 MAKASSAR SELATAN - Athaya Banjarani Putri, Afnin; Badollahi, Ismail; Japar, Rahayu (STKIP Subang, 2026)
This study examines the effects of financial literacy and financial planning on retirement financial readiness, with financial attitude as a mediating variable, among employees of PT PLN (Persero) UP3 Makassar Selatan. A quantitative approach was employed using questionnaire-based data collected from 72 respondents selected through a saturated sampling technique. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that financial literacy and financial planning significantly enhance retirement financial readiness. Financial literacy also exerts a positive effect on financial attitude, whereas financial planning shows no significant influence on financial attitude. In addition, financial attitude positively affects retirement financial readiness. However, it does not mediate the relationships between financial literacy and financial planning and retirement financial readiness.